The principle of non-interference in ASEAN: Can Malaysia spearhead the effort towards a more interventionist ASEAN - Othman, Muhammad Fuad; Othman, Zaheruddin (Institute of Tun Dr. Mahathir Mohamad's Thought (IPDM), Universiti Utara Malaysia (UUM), 2010)
The principle of non-interference in the internal aff airs of ASEAN member states has been identified as among the most significant element that shaped ASEAN intra relations and still remain very much appreciated. By not allowing member states to interfere into another’s internal affairs, especially into politico-security issues, it has created a stable and secured environment in the region which contributed tremendously to the efforts of national building and economic development. However, several regional incidents such as the 1997 Asian Economic Crisis, the spread of the Severe Acute Respiratory Syndrome (SARS), Indonesian Smog/Haze crisis and the Myanmar internal political quandary have questioned if not shaken the belief that the doctrine of non-interference is an untouchable sacred political arrangement. This paper will investigate the genesis of this doctrine, the incidents that challenge the doctrine and Malaysia’s readiness as a country to lead changes in the doctrine.